Video-assisted laparoscopy for the detection and diagnosis of endometriosis: safety, reliability, and invasiveness - Schipper E; Nezhat C (Dove Medical Press, 2012)
Erica Schipper,1 Camran Nezhat21Center for Minimally Invasive and Robotic Surgery, Palo Alto, CA; 2Obstetrics/Gynecology and Surgery, Stanford University Medical Center, Palo Alto, CA, USAAbstract: Endometriosis is a highly enigmatic disease with multiple presentations ranging from infertility to severe pain, often causing significant morbidity. Video-assisted laparoscopy (VALS) has now replaced laparotomy as the gold standard for the diagnosis and management of endometriosis. While imaging has a role in the evaluation of some patients, histologic examination is needed for a definitive diagnosis. Laboratory evaluation currently has a minor role in the diagnosis of endometriosis, although studies are underway investigating serum markers, genetic studies, and endometrial sampling. A high index of suspicion is essential to accurately diagnose this complex condition, and a multidisciplinary approach is often indicated. The following review discusses laparoscopic diagnosis of endometriosis from the pre-operative evaluation of patients suspected of having endometriosis to surgical technique for safe and adequate laparoscopic diagnosis of the condition and postsurgical care.Keywords: endometriosis, video-assisted, laparoscopy, diagnosis